Implementing digital respiratory technologies for people with respiratory conditions: A protocol for a scoping review. - Chi Yan Hui; Kathleena Condon; Shailesh Kolekar; Nicola Roberts; Katherina Bernadette Sreter; Sami O Simons; Carlos Figueiredo; Zoe McKeough; Hani Salim; Aleksandra Gawlik-Lipinski; Apolline Gonsard; Ayşe Önal Aral; et al. (PLoS ONE)
The value of 'data-enabled', digital healthcare is evolving rapidly, as demonstrated in the COVID-19 pandemic, and its successful implementation remains complex and challenging. Harmonisation (within/between healthcare systems) of infrastructure and implementation strategies has the potential to promote safe, equitable and accessible digital healthcare, but guidance for implementation is lacking. Using respiratory technologies as an example, our scoping review process will capture and review the published research between 12th December 2013 to 12th December 2023. Following standard methodology (Arksey and O'Malley), we will search for studies published in ten databases: MEDLINE, EMBASE, CINAHL, PsycINFO, Cochrane Library, Web of Science, Scopus, IEEE Xplore, CABI Global Health, and WHO Medicus. Our search strategy will use the terms: digital health, respiratory conditions, and implementation. Using Covidence, screening of abstracts and full texts will be undertaken by two independent reviewers, with conflicts resolved by a third reviewer. Data will be extracted into a pilot-tested data extraction table for charting, summarising and reporting the results. We will conduct stakeholder meetings throughout to discuss the themes emerging from implementation studies and support interpretation of findings in the light of their experience within their own networks and organisations. The findings will inform the future work within the ERS CONNECT clinical research collaboration and contribute to policy statements to promote a harmonised framework for digital transformation of respiratory healthcare.